Analisis Distorsi Kebijakan Pemerintah Provinsi dengan Pemerintah Kabupaten terhadap Proyek PLTPB - Rofingi, Rofingi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Post-reforms goverment authority in Indonesia were no longer centralized. Decentralization then emerged as dispersion of the central goverment affairs to the regional goverment. This article discusses the incompatibility of the Geothermal Power Plant (PLTPB) project issued by the district / city government but was issued by the provincial government using the normative-analysis method. Government concurrent affairs are divided into two affairs; compulsory and optional. The existence of PLTPB in Banyumas district is one of the democratic matters of choice. One of PLTPB problems is that the regent of Banyumas do not aware of PLTPB policy. It can be seen that there is no synchronization and harmonization between the provincial and district /city governments. Negative impacts ranging from destruction of residents' land to river pollution are not handled. The authority of these provisions must be taken over by the regency / city government and there must be countermeasures against affected people so that good governance will be created.